Relating Environmental Changes on Human Health – A Global Clustering Analysis - Munir, Mubbasher; Fahmida; Nisar, Haseeb (Pakistan Journal of Humanities and Social Sciences, 2024)
Green Environment is a dream of the modern world but there are several direct and indirect environmental factors affecting our health. For this purpose, this study is efficiently highlighted key environmental indicators, those are caused to increase or decrease human obesity (globesity) in global prospective. This study plays a key role by collecting several global databases of 183 countries based on the availability data from the World Health Organization, World Development Indicators by World Bank and other sources. This study has used principal axis factoring (PAF), correlations, advanced visualizations and global clustering. The results show that global environment index has indirect relationship with globesity. The results also shown that low human developed countries have low effect of obesity, but very high human developed countries have high level of globesity. This is concluded that if environment index is increasing then human obesity at high risk and sown at high levels of correlation in global prospective at all HDI countries.